2018
DOI: 10.15171/ajehe.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reactive Blue 203 Dye Removal Using Ultraviolet Irradiation, Ferrate (VI) Oxidation Process and MgO Nanoparticles

Abstract: This study investigated the effect of various parameters on the removal of Reactive Blue 203 dye from wastewater using ferrate(VI) oxidation process, ultraviolet radiation (UV) radiation and MgO nanoparticles under batch mode. Although several studies have been carried out on dye removal, there is no study on the removal of Reactive Blue 203 dye using ferrate(VI) oxidation process, UV radiation, and MgO nanoparticles. Therefore, the aim of this study is to investigate the effect of different factors inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Some studies have used MgO nanoparticle as a catalyst for degrading organic pollutions in photocatalytic processes (26,27). These studies clearly indicated that photocatalytic processes using MgO nanoparticles increased the efficiency of organic pollutants from an aqueous medium.…”
Section: Introductionmentioning
confidence: 97%
“…Some studies have used MgO nanoparticle as a catalyst for degrading organic pollutions in photocatalytic processes (26,27). These studies clearly indicated that photocatalytic processes using MgO nanoparticles increased the efficiency of organic pollutants from an aqueous medium.…”
Section: Introductionmentioning
confidence: 97%